The Prophet's Mawlid: Integration of Spiritual, Cultural, and Character Education Values in Indonesian Multicultural Society - Moh. Subthi Buchori, Iffatul Lailiyah (PRODI PAI FIK UNIRA MALANG, 2025)
Character education in Indonesia faces complex challenges in the era of globalization, while the potential of local traditions as learning media has not been utilized optimally. This study aims to analyze the role of the tradition of the Prophet Muhammad's Mawlid as a contextual and inclusive medium for character education in Indonesian multicultural society. The research uses a descriptive qualitative approach with a literature study method, analyzed through content and thematic analysis techniques. The results show that Mawlid is a form of acculturation between Islam and Nusantara culture, rich in educational values such as religiosity, tolerance, and mutual cooperation. This tradition functions as a social laboratory for practicing character values, an effective medium for cultural propagation (dakwah), and a unifying vessel for the nation that revitalizes Pancasila values. The research concludes by underlining that Mawlid is a living tradition relevant for strengthening national character, with significant implications for the development of character education and national cultural policies based on local wisdom.